Persepsi Mahasiswa Pendidikan Bahasa dan Sastra Indonesia terhadap Pemanfaatan Teknologi ChatGPT dalam Menulis Karya Ilmiah di Universitas Negeri Makassar - Suarti, Putri; Djumingin, Sulastriningsih; Azis, Azis (Nuances of Indonesian Language, 2025)
This research aims to describe the perceptions of Indonesian Language and Literature Education students class of 2023 at Makassar State University regarding the use of ChatGPT technology in writing scientific papers. In this study, perception was measured through 6 indicators, namely: attitude, motivation, experience, expectations, goals and situation. The population in this study was 216 Indonesian Language and Literature Education students class of 2023, Makassar State University, a sample of 54 students taken using purposive sampling technique. This research uses a survey method, where the researcher describes the research data quantitatively through percentages and tables. Data collection was carried out by distributing questionnaires to respondents. The research results show that Indonesian Language and Literature Education students have a positive perception of the benefits of ChatGPT in writing scientific papers. Of the 54 respondents, 42 respondents (77.8%) had a positive perception and 12 respondents (22.2%) had a negative perception. Thus, the perception of Indonesian Language and Literature Education students class of 2023 at Makassar State University regarding the benefits of ChatGPT in writing scientific papers can be categorized as good.